Carbon and Nitrogen Sources Influence Tricalcium Phosphate Solubilization and Extracellular Phosphatase Activity by Talaromyces flavus - Stefanoni Rubio, Pablo Jose (2015)
The aim of this work was to study phosphate (P) solubilization (and the processes involved in this event) by Talaromyces flavus (BAFC 3125) as a function of carbon and/or nitrogen sources. P solubilization was evaluated in NBRIP media supplemented with different carbon (glucose, sorbitol, sucrose, and fructose) and nitrogen (l-asparagine, urea, ammonium sulfate (AS), and ammonium nitrate (AN) combinations. The highest P solubilization was related to the highest organic acid production (especially gluconic acid) and pH drop for those treatments where glucose was present. Also P solubilization was higher when an inorganic nitrogen source was supplemented to the media when compared to an organic one. Although not being present an organic P source, phosphatase activity was observed. This shows that P mineralization and P solubilization can occur simultaneously, and that P mineralization is not induced by the enzyme substrate. The combination that showed highest P solubilization was for AN-glucose. The highest acid phosphatase activity was for AS-fructose, while for alkaline phosphatase were for AS-fructose and AN-fructose. Acid phosphatase activity was higher than alkaline. P solubilization and phosphatase activity (acid and alkaline) were influenced by the different carbon–nitrogen combinations. A better understanding of phosphate-solubilizing fungi could bring a better use of soil P.